HUBUNGAN PERSEPSI PENERAPAN METODE TGT, TEKNIK REWARD AND PUNISHMENT DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS V SDN I NGREJO TULUNGAGUNG - Hendrik Eko Prasetyo (Universitas Islam Balitar, 2015)
The objective of this study is to analyze relationship between perception in implementing TGT, Reward and Punishment techniques, learning motivation toward learning achievement in Civic education subject. The study took place in SDN I Ngrejo Tulungagung assigning the 34 fifth graders. This study used correlational design and data were collected using questionnaire and test. Data were analyzed using multiple regression techniques. The study found that (1) positive relationship between TGT, reward and punishment and learning achievement exists at .946; (2) positive relationship between learning motivation and learning achievement is .965; (3) positive relationship altogether between TGT, reward and punishment, and learning motivation towards learning achievement is .844.